Penggunaan Sistem Informasi Geografis (SIG) dalam Mengestimasi Daya Dukung Habitat Gajah Sumatera (Elephas maximus sumatranus Temminck) Sebagai Salah Satu Alternatif Solusi Konflik dengan Lahan Pertanian - Abdullah Abdullah; Joko T. Iskandar; Devi N. Choesin; A. Sjarmidi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
Human elephant conflict surrounding agriculture and forest became higher a long year. The fenomena cannot be solved until now. We proposed new technigue, Geographic Information System (GIS)  for solving the problem mainly in agriculture area. The aim of this research for estimating habitat carrying capacity of Sumatran elephant habitat (Elephas maximus sumatranus Temminck) using Geographic Information System. Habitat and animal parameter estimated consist of biotic and abiotic factors. The factors analized suitability analysis using software Autocad Map 2000 and Arcview 3.1. this research result showed habitat carrying capacity in secondary forest (wet season :0,89±0,11 s.d 0,96±0,12 elephant/km²; dry:0,55±0,07 s.d 0,59 ± 0,08 elephant/km²) higher than primary forest (wet season: 0,20±0,02 to 0,26±0,05 elephant/km²  dry: 0,09±0,01 s.d 0,11±0,02 ind/km²). Based on suitability analysis estimated elephant carrying capacity in Tessonilo Forest in wet season (689,45±51,67 to 750,05± 109,14 elephants) higher than dry season (397,85 ±48,45 to 434,88±61,51 elephants). Elephant numbers fluctuated seasonally can be used for planting time strategy in agrculture system. The estimation of habitat carrying capacity did not consider habitat use seasonally.